Respuesta :
Answer:
The correct option will be: C. 3
Step-by-step explanation:
The given table is..........
[tex]x :[/tex] -6 -3 -1 0 1 4
[tex]f(x) :[/tex] 27 6 2 3 6 27
The formula for average rate of change is: [tex]\frac{f(b)-f(a)}{b-a}[/tex] , where [tex][a,b][/tex] is the given interval.
Here the interval is [-3, 4]. So, [tex]a=-3[/tex] and [tex]b=4[/tex]
Now, plugging the values of [tex]a[/tex] and [tex]b[/tex] into the above formula, we will get........
[tex]\frac{f(4)-f(-3)}{4-(-3)}[/tex]
From the given table, we will get [tex]f(4)=27[/tex] and [tex]f(-3)=6[/tex]
So, the average rate of change will be: [tex]\frac{27-6}{4-(-3)}= \frac{21}{7}=3[/tex]
Answer:
The person that answered it above me is correct
Step-by-step explanation: